The Influence of E-Banking and Service Quality on Loyalty in Customers of Bank Bri Unit Bukit Kemuning Lampung Utara - Widayanti, Ayu; Alam, Iskandar Ali (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to identify and analyze the influence of E-Banking and service quality on customer loyalty at Bank BRI Bukit Kemuning Unit, North Lampung. The use of technology in the banking sector, especially E-Banking, has become an integral part of banks' strategies in improving services to customers. Service quality is also recognized as a key factor influencing customer satisfaction and loyalty. The research method used was a survey by distributing questionnaires to 40 BRI Bank Bukit Kemuning Unit customers. The data collected was then analyzed using the regression method to determine the influence of the independent variable (X1) E-Banking on the dependent variable (X2) service quality (Y) customer loyalty. By using Validity Test, Reliability Test, Multiple Linear Regression Analysis, T Test (Partial), F Test (simultaneous), Coefficient of Determination (R Square). The research results show that E-Banking has a positive and significant influence on customer loyalty. The better the acceptance and use of E-Banking by customers, the higher their level of loyalty to the bank.